Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Corrigendum to “High-performance of starch-protein edible films with interpenetrating networks via reactive extrusion for food milk powder preservation” [Food Chem. 509 (2026) 148621] - Xuliang Wang; Yanxi Wang; Wenya Ma; Kunpeng Qian; Jiahao Zhang; Qingfeng Dong; Min Fan; Li Li (Food Chemistry, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

Sustainable Fertilization in Double-Cropping Vegetable System: Evidence from A 5-Year Tomato–Brassica Campestris Field Experiment - Lijun Ren; Lili Dong; Roland Bol; Qingfeng Fan; Dan Wei; Hongtao Zou (Journal of Soil Science and Plant Nutrition, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Defect-mediated rigid-flexible coupled architecture for upcycling of spent O3-type sodium-ion cathodes - Qingfeng Liu; Jinhua Shi; Fanbin Hu; Zitong Fei; Yun Shen; Haigang Dong; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2026)

Bio-organic fertilizer regulates nutrient accumulation and microbial communities across soil aggregate in intensive vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Plant and Soil, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Synergistic effects of the dual pilot policy on pollution reduction and carbon mitigation: The role of data empowerment and market mechanisms - Qingfeng Luo; Fenfen Wang; Can Wang; Xinyang Dong (Journal of Cleaner Production, 2026)

High-performance of starch-protein edible films with interpenetrating networks via reactive extrusion for food milk powder preservation - Xuliang Wang; Yanxi Wang; Wenya Ma; Kunpeng Qian; Jiahao Zhang; Qingfeng Dong; Min Fan; Li Li (Food Chemistry, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

Bio-organic fertilization promotes soil nutrient cycling and reduces CO2 emissions via regulating bacterial communities in vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (European Journal of Soil Biology, 2026)

Multi-trait analysis to identify key factors influencing wheat lodging resistance and validation of an integrative lodging index - Hao Ren; Qingfeng Dong; Siting Li; Dezheng Liu; Xubin Zhang; Xue Wang; Liang Chen; Yin-Gang Hu (European Journal of Agronomy, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Double-plunging structure of the Bond 4 event evidenced in new mid-Holocene stalagmite records from northern China - Quan Wang; Yingfang Cui; Kan Zhao; Jianshun Chen; Qingfeng Shao; Jianghu Lan; Liangcheng Tan; Lei Ding; Hongan Dong; Lili Dai; Yongjin Wang (Global and Planetary Change, 2025)

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

The WRKY gene family members in Panax quinquefolius L.: identification, evolution, and expression analysis in response to rusty root rot disease - Yuxue Pang; Lei Chen; Qingfeng Zhang; Yukun Dong; Hongtao Wang (Horticulture, Environment, and Biotechnology, 2025)

Persistently centennial to millennial variability of Asian summer monsoon and north-south coupling during the late penultimate glacial period - Wei Huang; Zhenqiu Zhang; Kan Zhao; Yongjin Wang; Qingfeng Shao; Jinguo Dong; Xiuyang Jiang; Xiumin Zhai; Carlos Pérez-Mejías (Global and Planetary Change, 2025)

Thiazolyl-conjugated porous polymer-coated CdZnS for synergistic adsorption and photocatalytic degradation of bisphenol A and with enhanced H2O2 production - Wanjun Xu; Yingxue Zhang; Shihong Dong; A.S. Gubin; I.N. Pugacheva; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Deciphering the regulatory network of carbon isotope discrimination in bread wheat through genome-wide association studies and genomic prediction - Qingfeng Dong; Shan Lu; Hao Ren; Dezheng Liu; Shen-ao Gao; Xuefen Cai; Shanshan Zhang; Muhammad Ateeq; Liang Chen; Yin-gang Hu (Theoretical and Applied Genetics, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

The synergistic effect of vacuum skin packaging and electrospun film on the quality of grass carp (Ctenopharyngodon idellus) surimi during refrigerated storage - Qingfeng Dong; Xiao Wang; Wenya Ma; Li Li (Food Research International, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Deciphering the regulatory network of lignocellulose biosynthesis in bread wheat through genome-wide association studies - Qingfeng Dong; Hao Ren; Xuefen Cai; Yujie Zhang; Shan Lu; Dezheng Liu; Muhammad Ateeq; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Large-scale dual-responsive ClO2 controlled-release film for strawberry preservation - Siqi Chen; Wenya Ma; Ying Cao; Kunpeng Qian; Qingfeng Dong; Li Li (Food Chemistry, 2025)

Enhancement of calcium alginate and urea in gel-modified dry water inhibition of methane-air explosion - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Chao Ma; Qingfeng Wang; Youjie Sheng; Dong Zhao (Process Safety and Environmental Protection, 2025)

Efficient As(III) removal from acidic wastewater by polymorphism control of FeS - Jing Chen; Qingfeng Dong; Jing Li; Chaobo Zhang; Guang Fu; Zhanqing Lu (Journal of Water Process Engineering, 2025)

Mining genomic regions associated with stomatal traits and their candidate genes in bread wheat through genome-wide association study (GWAS) - Dezheng Liu; Shan Lu; Renmei Tian; Xubin Zhang; Qingfeng Dong; Hao Ren; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

High strength and water tolerance fish gelatin-xanthan gum acid-induced electrostatic film by melt extrusion method - Xiaohan Chen; Zhuolin Liu; Wenya Ma; Hao Wang; Qingfeng Dong; Li Li (Food Hydrocolloids, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

n-Acetylcysteine protects against diazinon-induced histopathological damage and apoptosis in renal tissue of rats - Gaiqin Dong; Qingfeng Li; Chun Yu; Qing Wang; Danhua Zuo; Xiaozhong Li (Toxicological Research, 2024)

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Development of electrospun fish gelatin film containing lauroyl arginate ethyl and its application in large yellow croaker (Pseudosciaena crocea) preservation - Qingfeng Dong; Lan Yang; Leiwen Xiang; Yueliang Zhao; Li Li (Food Control, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Melt blending crystallization regulating balanced nanodomains in efficient and scalable coating processed organic solar cells - Anran Wang; Yifei Kang; Chunqing Hou; Rong Li; Yilong Song; Qingfeng Dong (Science Bulletin, 2023)

Development of organic-inorganic hybrid antimicrobial materials by mechanical force and application for active packaging - Weizhong Zhu; Jiali Chen; Qingfeng Dong; Donglei Luan; Ningping Tao; Shanggui Deng; Li Wang; Yi Hao; Li Li (Food Packaging and Shelf Life, 2023)

Experimental Study on the Influence of Temperature on Rock Salt Creep - Zhikai Dong; Yinping Li; Haoran Li; Ziheng Wang; Xilin Shi; Xiangsheng Chen; Qingfeng Lu (Rock Mechanics and Rock Engineering, 2023)

Loofah sac-like three-dimensional interwoven network composed of Van-PEG-MWCNTs for rapid and efficient capture of Staphylococcus aureus - Yu Chen; Yong Liu; Qingfeng Dong; Min Fan; Li Li (Food Bioscience, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Late Cretaceous K-rich rhyolitic crystal tuffs from the Chuduoqu area in Eastern Qiangtang subterrane: evidence for crustal thickening of the central Tibetan Plateau prior to India–Asia collision - Yonggang Sun; Bile Li; Fengyue Sun; Qingfeng Ding; Junlin Dong; Ye Qian; Yujin Li; Zhen Yao (Acta Geochimica, 2022)

Correction to: MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

GelMA combined with sustained release of HUVECs derived exosomes for promoting cutaneous wound healing and facilitating skin regeneration - Danyang Zhao; Zhencheng Yu; Yun Li; Yu Wang; Qingfeng Li; Dong Han (Journal of Molecular Histology, 2020)

Distribution of water-stable aggregates under soil tillage practices in a black soil hillslope cropland in Northeast China - Lei Yan; Xuexin Jiang; Xiaonan Ji; Liting Zhou; Siying Li; Chen Chen; Peiye Li; Yuanchen Zhu; Tianhao Dong; Qingfeng Meng (Journal of Soils and Sediments, 2020)

A new azaphilone from the entomopathogenic fungus Hypocrella sp. - Qingfeng Guo; Lili Dong; Xiangyun Zang; Zijian Gu; Xiaoyun He; Lindan Yao; Liping Cao; Junzhi Qiu; Xiong Guan (Natural Product Research, 2015)

Cooperation among Numb, MDM2 and p53 in the development and progression of pancreatic cancer - Weiwei Sheng; Ming Dong; Jianping Zhou; Xin Li; Qingfeng Liu; Qi Dong; Feng Li (Cell and Tissue Research, 2013)

Daidzein Induced Apoptosis via Down-Regulation of Bcl-2/Bax and Triggering of the Mitochondrial Pathway in BGC-823 Cells - Shuyao Tang; Jing Hu; Qingfeng Meng; Xuesong Dong; Kaifu Wang; Yuebin Qi; Chao Chu; Xiaochuan Zhang; Limin Hou (Cell Biochemistry and Biophysics, 2013)